A phylogeographic study of the stoneplant Conophytum (Aizoaceae; Ruschioideae; Ruschieae) in the Bushmanland Inselberg Region (South Africa) suggests anemochory. Issue 2 (17th February 2019) - Powell, Robyn F.; Magee, Anthony R.; Forest, Felix; Cowan, Robyn S.; Boatwright, J. Stephen
Abstract : The Bushmanland Inselberg Region (BIR) of South Africa provides an ideal system to study population interactions, as these inselbergs function as islands of Succulent Karoo surrounded by Nama Karoo vegetation. The population genetics of four Conophytum taxa endemic to the quartz-associated habitats of inselbergs in the BIR were investigated using amplified fragment length polymorphisms (AFLP), namely C. marginatum subsp. haramoepense, C. marginatum subsp. marginatum, C. maughanii, and C. ratum . Conophytum marginatum colonizes the quartz outcrops on the summits of the inselbergs, while C. maughanii and C. ratum occupy quartz patches at the summit and base of the inselbergs. A total of 24 populations were sampled to assess genetic differentiation between populations of each species, specifically between summit and base populations of C. ratum, eastern and western populations of C. maughanii and populations of the two subspecies of C. marginatum . Moderate levels of genetic differentiation were recovered between the summit and base populations of C. ratum, with an indication of some genetic connectivity between the populations. Slight differentiation between the eastern and western populations of C. maughanii was recovered, however, this was not reflected in the PCoA and STRUCTURE results. In C. marginatum, no significant genetic differentiation was recovered between populations of the subspecies. These results may reflect evidence of different dispersal mechanisms in the species, with the genetic connectivity between populations of C. ratum possibly indicating dispersal through hygrochastic capsules, while genetic connectivity between populations of C. maughanii and C. marginatum may, for the first time, suggest long-distance dispersal, i.e. anemochory. This study provides the first insights into population interactions across the BIR and highlights the importance of conservation in the region, particularly of the Gamsberg, in light of the recent mining activities.